Drug treatments for acne vulgaris in adolescents and young adults (Research, Society and Development, 2021)
Objective: To describe the drug treatments available for acne vulgaris in adolescents and young adults. Methodology: this is an integrative review, with searches in the databases: Medical Literature Analysis and Retrieval System (MEDLINE/PubMed), Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Literature in Health Sciences (LILACS), using Health Sciences Descriptors (DECS): “acne vulgar”, “terapêutica”, “adolescentes” e “adulto jovem”, combined through Boolean operators, from 2015 to 2020. Results: Were selected 15 articles. Because it is a disease of multifactorial etiology, several therapies need to be adopted for effective treatment. The available treatments involve retinoids, antibiotics, corticosteroids, benzoyl peroxide, adapalene, oral contraceptives, formulations of natural extracts, strains of bacteria, nanoparticles, including topical and systemic treatments. Conclusion: the treatments for acne vulgaris are multiple and varied, and have been improved and even more diversified, however, the need for more scientific studies to develop effective treatments with fewer side effects is emphasized, contributing to accessibility and greater adherence affected.